The Sociomateriality of Justice: A Relational Ontology for Legal Design: A Relational Ontology for Legal Design - Santuber, Joaquin; Krawietz, Lina (RChD: creación y pensamiento, 2021)
Legal and justice Design is best positioned as a post-disciplinary and nomadic practice. This paper offers a relational ontology for Legal Design practices and studies. Building on conceptual frameworks from gender studies, philosophy, and organizational research, we account for the sociomateriality of justice in Chilean courts. With this, we aim to overcome the limitations to the impact of such studies on justice imposed by their disciplinary fixation in terms of methodologies, and onto-epistemologies. In this regard, we understand the sociomateriality of justice as performative practices, configurations of human and non-human agency, situated action and affects, and apparatuses and diffraction. For each we provide examples from an in-depth case study on Chilean courts, the Communications Department of the Supreme Court, and a law clinic working with victims of sexual abuse. Our contribution is twofold. First, we draw on diverse literature to propose a relational approach to Legal Design, grounded in sociomateriality. Second, with the case study, we advance the understanding of the emergence of local practices in courts and their materiality. In addition, we highlight the implications for Legal Design practice and studies.